What makes cities bigger and richer? New Evidence from 1990-2000 in the US - Rafael González-Val (European Regional Science Association (ERSA), 2011)
This paper analyses the determinants of growth of American cities, understood as growth of the population or of per capita income, from 1990 to 2000. This empirical analysis uses data from all cities with more than 25,000 inhabitants in the year 2000 (1154 cities). The results show that while a common convergence behaviour is observed in both population and per capita income growth, there are differences in the evolution of the distributions: population distribution remains almost unchanged, while per capita income distribution makes a great movement to the right. We propose two hypotheses related with the influence of service activities and geography on urban growth, and test them with different empirical methods: linear models and Multinomial Logit Models.
Keywords: 330